1996
DOI: 10.1148/radiology.198.2.8596830
|View full text |Cite
|
Sign up to set email alerts
|

Composition of mammographic phantom materials.

Abstract: A phantom composed of 30% glandular tissue and 70% adipose tissue allows closer simulation of the phototimer response of the mammographic x-ray unit for the average breast. The phantom currently used contains 16% more glandular tissue than the average breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 0 publications
4
33
2
Order By: Relevance
“…A polynomial fit of the percent glandularity is used to predict the mean compressed breast thickness for any desired breast tissue composition. Geise and Palchevsky ( 4 ) reported that the width of the glandularity distribution increases for compressed thickness between 3 cm and 7 cm but is narrower above and below this range. The phantoms were assembled from 1‐cm thick slabs of homogeneous BRTES material, with one slab in each phantom having a thickness an appropriate fraction of a centimeter to produce noninteger centimeter thicknesses when desired.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A polynomial fit of the percent glandularity is used to predict the mean compressed breast thickness for any desired breast tissue composition. Geise and Palchevsky ( 4 ) reported that the width of the glandularity distribution increases for compressed thickness between 3 cm and 7 cm but is narrower above and below this range. The phantoms were assembled from 1‐cm thick slabs of homogeneous BRTES material, with one slab in each phantom having a thickness an appropriate fraction of a centimeter to produce noninteger centimeter thicknesses when desired.…”
Section: Methodsmentioning
confidence: 99%
“…( 4 ) Once phantoms representing the attenuation properties and densities of 0% and 100% glandularity were obtained, they were combined in linear combinations of fractional weight percentage in order to provide BRTES materials of the desired glandularity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations